The gut mucin-microbiota interactions: a missing key to optimizing endurance performance - Clark, Allison; Mach, Núria (Frontiers in Physiology, 2023)
Endurance athletes offer unique physiology and metabolism compared to sedentary individuals. Athletes training at high intensities for prolonged periods are at risk for gastrointestinal disturbances. An important factor in endurance performance is the integrity and function of the gut barrier, which primarily depends on heavily O-glycosylated mucins.Emerging evidence shows a complex bidirectional dialogue between glycans on mucins and gut microorganisms. This review emphasizes the importance of the crosstalk between the gut microbiome and host mucus mucins and some of the mechanisms underlying this symbiosis. The contribution of mucin glycans to the composition and functionality of the gut microbiome is discussed, as well as the persuasive impact of the gut microbiome on mucin composition, thickness, and immune and metabolic functions. Lastly, we propose natural and synthetic glycans supplements to improve intestinal mucus production and barrier function, offering new opportunities to enhance endurance athletes' performance and gut health.